HOW TO MAKE THE MACEDONIAN ECONOMY MORE ”GREEN” - Trenčeva, Nada; Krstevska, Martina (International Journal of Economic Practice and Policy, 2018)
Every economy has its own priorities that need to be met. One of the main priorities for every economy and Macedonian as well is to create sustainable economic development and environmental protection. Macedonia must implement an interdisciplinary approach including a lot of scientific disciplines and social activities in order to save its environment and to ensure a favorite economic development at the same time. The Environment Science and the Ecology Movement insist on measures to protect the environment, and the economic science insists on efficiency in operations. The aim of this paper is to use the statistical method and the method of comparison to get closer the opposing views and to present the efforts that Macedonia undertakes to integrate all aspects of the environment in all areas and at all levels. To fulfill this, Macedonia must set а several goals: to secure sustainable agricultural production; to use renewable and green energy, new technologies; to reducе the СO2 emissions; to promote clean innovation, еtc.